Self-esteem of fourth grade students in learning physical education - Dian Pujianto; Yahya Eko Nopiyanto; Hakas Riris Anggita Ningrum; Dwi Nevitasari (Altius: Jurnal Ilmu Olahraga dan Kesehatan, 2022)
Knowing the level of self-esteem of grade 4 students in participating in physical education learning is the main goal of this study. To achieve the research objectives used descriptive quantitative research methods. The research population involved in the data collection process was all 4th-grade students as many as 23 students. Meanwhile, total sampling was used for sampling so 23 students were used as research samples. A questionnaire consisting of 22 questions representing 7 indicators was used to collect data. While the data analysis technique uses the ideal mean value and standard deviation to classify the data obtained. The results of the data analysis illustrate that the indicators of self-satisfaction, positive emotions, and optimism are in the high category. While the indicators of interaction, dare to take risks, positive attitude and self-confidence are in the medium category. So, it was concluded that the level of self-esteem of grade 4 students participating in physical education learning at Elementary School 38 Bengkulu City was moderate.